2019
DOI: 10.1016/j.ajhg.2019.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Scan Procedure for Detecting Rare-Variant Association Regions in Whole-Genome Sequencing Studies

Abstract: Whole-genome sequencing (WGS) studies are being widely conducted in order to identify rare variants associated with human diseases and disease-related traits. Classical single-marker association analyses for rare variants have limited power, and variant-set-based analyses are commonly used by researchers for analyzing rare variants. However, existing variant-set-based approaches need to pre-specify genetic regions for analysis; hence, they are not directly applicable to WGS data because of the large number of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…The STAAR procedure is fast and scalable for very large WGS studies and biobanks of hundreds of thousands to millions of samples for both quantitative and dichotomous phenotypes as it uses estimated sparse GRMs 38 to fit the null GLMM and to scan the genome. Besides using sliding windows of a pre-specified fixed window length, STAAR could be extended to flexibly detect the sizes and locations of coding and non-coding rare variant association regions using the dynamic window analysis method SCANG 83 . In addition, STAAR could be extended to settings with survival, unbalanced case-control, and multiple phenotypes, and hence could provide a comprehensive framework for WGS RVAS.…”
Section: Discussionmentioning
confidence: 99%
“…The STAAR procedure is fast and scalable for very large WGS studies and biobanks of hundreds of thousands to millions of samples for both quantitative and dichotomous phenotypes as it uses estimated sparse GRMs 38 to fit the null GLMM and to scan the genome. Besides using sliding windows of a pre-specified fixed window length, STAAR could be extended to flexibly detect the sizes and locations of coding and non-coding rare variant association regions using the dynamic window analysis method SCANG 83 . In addition, STAAR could be extended to settings with survival, unbalanced case-control, and multiple phenotypes, and hence could provide a comprehensive framework for WGS RVAS.…”
Section: Discussionmentioning
confidence: 99%
“…where ω k represents the nonnegative weight for each p k with and K = 5; in the absence of prior knowledge, the equal weights are adapted, and assume that ω k is not related to p k . It has been theoretically demonstrated that the dependency among p -values imposes little influence on the final pooled p -values in ACAT, especially on exceedingly small p -values which are of particular interest for practitioners ( Li et al, 2019 ; Liu et al, 2019 ). Therefore, ACAT renders the potential to allow us to aggregate correlated p -values obtained from multiple tests into a single well-calibrated p -value that can maintain the type I error control correctly.…”
Section: Methodsmentioning
confidence: 99%
“…We use a scan statistics approach to identify regions showing correlated effects between different traits. This type of approach has been used for burden test in a single-trait setting 77 . Suppose ( , * are the sample sizes for two GWASs, respectively, and we first consider the simpler case that there is no sample overlap between two GWASs.…”
Section: Scan Statistic and Scanning Proceduresmentioning
confidence: 99%